A qualidade de água como indicador de uso e ocupação do solo : bacia do Gama - Distrito Federal - Moura, Luiz Henrique Amorim (2010)
The spread of Brasília isn't accompanied by correct support of land occupation, situation that is reflected in water quality. Under the optics of land use and occupation, working with multivariate statistics as main tool, water physical and chemical quality of Gama Catchment were assessed. During two years samples were collected and analyzed for 24 parameters. The statistical analysis showed the influence of civil buildings, agricultural activities and the best statistical parameters to a quickly assessment: nitrate, ammonia, suspended solids and aluminium.